2022
DOI: 10.3389/fspor.2022.867140
|View full text |Cite
|
Sign up to set email alerts
|

Training Patterns and Mental Health of Bodybuilders and Fitness Athletes During the First Lockdown of the COVID-19 Pandemic—A Cross-Sectional Study

Abstract: Background:Government restrictions during the first COVID-19 lockdown, such as the closure of gyms and fitness centers, drastically limited the training opportunities of bodybuilders and fitness athletes (BoFA) who rely on indoor training facilities. This provided a unique situation to investigate the effect of training limitations on the training patterns, training adaptive strategies and mental health of BoFAs.ObjectivesThe primary aim of this study was to investigate differences in the training patterns and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…While some studies have investigated the effects of COVID-19 on physical fitness in children 10 , research focusing on standardised fitness testing in adult populations is scarcer due to insufficient data. Moreover, most studies that have examined this topic have relied on subjective fitness questionnaires to assess acute changes 11 , 12 . Although qualitative research has provided valuable insights into how individuals’ behaviours might be affected by the pandemic and lockdowns, it falls short of providing an accurate representation of fitness changes compared with objective measurements.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have investigated the effects of COVID-19 on physical fitness in children 10 , research focusing on standardised fitness testing in adult populations is scarcer due to insufficient data. Moreover, most studies that have examined this topic have relied on subjective fitness questionnaires to assess acute changes 11 , 12 . Although qualitative research has provided valuable insights into how individuals’ behaviours might be affected by the pandemic and lockdowns, it falls short of providing an accurate representation of fitness changes compared with objective measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The study discovered that BoFA members’ financial worries increased during the lockdown, with about 32% of them depending on their athletic endeavors for income. BoFA also scored highly on measures of depression, insomnia, and anxiety, which may be due to the loss of the protective effect of physical activity on mental health or the psychological impact of being unable to train (11). Finally, the study found that individuals at risk for muscle dysmorphia performed worse and scored higher on tests of anxiety, insomnia, and depression compared to those without the disorder (11).…”
Section: Resultsmentioning
confidence: 99%
“…The concern for physical appearance and aesthetics is a phenomenon that is increasingly common today. In fact, dissatisfaction with physical appearance and the pursuit of aesthetic perfection can have serious consequences for individuals’ health [ 4 ]. Body satisfaction plays a crucial role in mental health, contributing to self-esteem and overall well-being [ 5 ].…”
Section: Introductionmentioning
confidence: 99%